Development and Evaluation of Polyherbal Formulation for the Management of Chronic Disorder (Diabetes) - Sharma, Mohit; Sahu, Ratnesh; Khan, Talah; Khakre, Nikhil; Tiwari, Dr. Pankaj (American Journal of Biomedicine and Pharmacy, 2025)
Polyherbal formulation having more than one plant in the particular dosage form. These formulation shows greater therapeutic efficacy compared to single plant. In the present study it was intended to formulate antidiabetic polyherbal formulation incorporating different ratio of the Annona squamosa (leaves), Withania somnifera (roots), Tinospora cordifolia (stems)and Azadirachta indica (leaves). The seven different polyherbal formulation (HF1 to HF4) were prepared and administered orally to the streptozotocin induced diabetic rats. The experimental rats treated with the HF1 to HF4 and reference drug Glibenclamide significantly reduced the blood glucose level compared to the diabetic control group. Further, the HF1 to HF4 showed antihyperlipidemic activity by lowering the total cholesterol, triglycerides and low-density lipoprotein level as well asenhanced the high-density lipoprotein. The polyherbal formulations and reference drug improve the body wights of the rats.